Will centralized drug procurement policy improve enterprises’ total factor productivity? - Xin Li; Ran Tao; Wenxue Zou; Yuning Jin (Frontiers in Public Health)
Against the backdrop of China’s healthcare reform challenges in drug pricing, this study investigates the impact of the National Centralized Drug Procurement (NCDP) policy implemented in 2018. Employing Difference-in-Differences (DID) methodology on quarterly data from A-share listed pharmaceutical firms (2003-2021, sourced from WIND/CSMAR databases), we demonstrate that NCDP participation significantly reduces Total Factor Productivity . Robustness is confirmed through index substitution, propensity score matching, and lag tests. The negative effect is amplified in non-state-owned enterprises, non-TCM manufacturers, and firms with high analyst coverage. Mechanistically, NCDP suppresses TFP through: (i) tightened financing constraints (↑KZ index) impairing capital allocation efficiency, and (ii) an indirect pathway where short-term R&D surges (↑RD) trigger resource crowding-out effects, compounded by diminished investment efficiency (↑INV), ultimately forming an “R&D→investment inefficiency→TFP↓” transmission chain. To reconcile public welfare objectives with corporate sustainability, we propose dual optimization strategies: differentiated financing support and innovation incentive reform. These establish a sustainable equilibrium between price control and TFP enhancement, providing actionable solutions for nationwide NCDP scaling.